The Role of Empirical Albendazole Treatment in Idiopathic Hypereosinophilia - A Case Series - Eleonora Vaisben; Ronen Brand; Anas Kadakh; Faris Nassar (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hypereosinophilia is usually defined as a blood eosinophil count >1500/μL. A broad variety of conditions are associated with hypereosinophilia. The present report describes three cases of hypereosinophilia, in which a thorough history, physical examination, laboratory and imaging investigations were unable to detect any abnormalities. Albendazole was empirically administered in all three cases, with complete normalization of eosinophil counts thereafter. Empirical treatment with albendazole for patients presenting with hypereosinophilia should be strongly considered.